Osteoarthritis-associated basic calcium phosphate crystals alter immune cell metabolism - Kelly, Daniel; Mahon, Olwyn; McCarthy, Geraldine M.; Dunne, Aisling (My University, 2020)
A number of studies have demonstrated that molecules called ‘alarmins’ or danger-associated molecular patterns (DAMPs), contribute to inflammatory processes in the OA joint. Metabolic reprogramming of immune cells, including macrophages, is emerging as a prominent player in determining immune cell phenotype and function. The aim of this study was to investigate if basic calcium phosphate (BCP) crystals which are OA-associated DAMPs, impact on macrophage phenotype and metabolism.
PUBLISHED
Keywords: ‘alarmins’ or danger-associated molecular patterns (DAMPs); Immunometabolism; Macrophage polarization; BCP crystals; Metabolic reprogramming